Does It Get Better? Recent Estimates of Sexual Orientation and Earnings in the United States. (18th August 2017) - Carpenter, Christopher S.; Eppink, Samuel T.
Abstract : Using 2013–2015 National Health Interview Survey data, we reproduce a well‐documented finding that self‐identified lesbians earn significantly more than comparable heterosexual women. These data also show— for the first time in the literature— that self‐identified gay men also earn significantly more than comparable heterosexual men, a difference on the order of 10% of annual earnings. We discuss several possible explanations for the new finding of a gay male earnings premium and suggest that reduced discrimination and changing patterns of household specialization are unlikely to be the primary mechanisms.